Development of social responsibility in Latin American companies: A systematic review between the years 2010 - 2020 - Vargas Merino, Jorge Alberto (2021)
Companies in Latin America cannot ignore the need to develop corporate social responsibility because this form of management promotes respect for nature and commitment to humanity. Several companies have problems in the development of CSR because there is confusion between social responsibility and philanthropy. The aim is to analyse theoretical and empirical studies on the development and application of corporate social responsibility in Latin American companies between 2010 and 2020. The sources of information are the databases EBSCOhost, Dialnet, ProQuest, Redalyc and Scielo, the criteria for eligibility were: place Latin America, period of the last 10 years and evaluated by experts, therefore those that did not meet these criteria were excluded. One of the limitations found was in the sub-theme dimensions, it was evident that there is no theoretical consensus regarding the parts contained in this approach. In conclusion, social responsibility is developing with some confusion as there is no internationally agreed standard for its concept. Finally, the present research should be deepened with an empirical statistical study in order to quantify the effects of the variable.